ANALYSIS OF E-AUDIT IMPLEMENTATION FOR STATE FINANCIAL AUDIT STUDY AT BPK RI REPRESENTATIVE OF THE SPECIAL REGION OF YOGYAKARTA - Siti Mubiroh (Berkala Akuntansi dan Keuangan Indonesia, 2019)
The Supreme Audit Agency (BPK) of the Republic of Indonesia has an important role in increasing the accountability of state finances. In carrying out its duties, BPK faces problems, namely limited human resources and relatively short inspection times. Therefore, BPK has developed an e-audit information system in carrying out audits of state financial management and responsibility. This study uses the DeLone and McLean (2003) Information System Success Model using six components, namely System Quality, Information Quality, Service Quality, Information System Use, User Satisfaction, and Net Benefits. The difference between this research and previous research is that this research uses a qualitative approach with a case study method with the aim of knowing the implementation of e-audit in depth. The sampling technique used snowball sampling. Data collection techniques using interviews, observation, and documentation. The informants in this study were the auditors of the BPK RI Representatives of Yogyakarta. The results of this study indicate that the main search feature and the inter-data feature are effectively used in the local government financial audit process, while the LKPD feature has not been effectively used in the regional government financial audit process.